Blueprints for Medieval hydroclimate - Seager, Richard; Graham, Nicholas E.; Herweijer, Celine; Gordon, Arnold L.; Kushnir, Yochanan; Cook, Edward R. (Columbia University, 2007)
According to tree ring and other records, a series of severe droughts that lasted for decades afflicted western North America during the Medieval period resulting in a more arid climate than in subsequent centuries. A review of proxy evidence from around the world indicates that North American megadroughts were part of a global pattern of Medieval hydroclimate that was distinct from that of today. In particular, the Medieval hydroclimate was wet in northern South America, dry in mid-latitude South America, dry in eastern Africa but with strong Nile River floods and a strong Indian monsoon. This pattern is similar to that accompanying persistent North American droughts in the instrumental era. This pattern is compared to that associated with familiar climate phenomena. The best fit comes from a persistently La Nin ̃ a-like tropical Pacific and the warm phase of the so-called Atlantic Multidecadal Oscillation. A positive North Atlantic Oscillation (NAO) also helps to explain the Medieval hydroclimate pattern. Limited sea surface temperature reconstructions support the contention that the tropical Pacific was cold and the subtropical North Atlantic was warm, ideal conditions for North American drought. Tentative modeling results indicate that a multi-century La Nina-like state could have arisen as a coupled atmosphere–ocean response to high irradiance and weak volcanism during the Medieval period and that this could in turn have induced a persistently positive NAO state. A La Nina-like state could also induce a strengthening of the North Atlantic meridional overturning circulation, and hence warming of the North Atlantic Ocean, by (i) the ocean response to the positive NAO and by shifting the southern mid-latitude westerlies poleward which (ii) will increase the salt flux from the Indian Ocean into the South Atlantic and (iii) drive stronger Southern Ocean upwelling.